ROBOTIC REPLICATION OF LIVING THINGS AND IMPLICATIONS FOR WARFARE (Margalla Papers, 2025)
The paper discusses nature-inspired robotic replications, their potential military applications, implications for warfare, and the perspective of International Humanitarian Law (IHL). Historically, animals have been used in war, helping to turn the tide of battles and the fortunes of many combat soldiers. However, in modern times, there is a growing interest in replicating characteristics of natural creatures in AI-enabled robotics for military purposes. Key mechanics of natural systems, such as manoeuvrability, agility, and aerodynamics, as well as intelligence factors like coordination, swarming, task sharing, and cooperation, have inspired the development of military robots. These robots, equipped with the instinct of survivability alongside features such as self-organization, self-adaptability, and self-learning, are well-suited to navigate the battlefield's challenges and engage in warfare despite the inherent unpredictability and chaos involved. By leveraging the evolutionary advantages of nature, military robots can enhance their effectiveness through biomimicry, as they tend to be more adaptable to unforeseen scenarios. This increased adaptability improves their ability to learn and evolve in response to environmental changes, thereby significantly enhancing mission outcomes. The findings of this research show that, in addition to presenting significant moral, ethical, and legal challenges, rapid advancements lead to the militarization of nature and significantly alter the nature of warfare. The study also provides recommendations for an international consensus on legally binding instruments. Bibliography EntryUllah, Atta and Sher Ali Kakar. 2025. "Robotic Replication of Living Things and Implications for Warfare." Margalla Papers 29 (1): 80-95.